Association between wooden toy engagement and cognitive function among Chinese older adults: a cross-sectional study - Wang, Hanqian; Cheng, Qiuping; Mei, Ping; Cui, Mengni; Wang, Qunlong; Li, Lu (Frontiers in Psychology, 2025)
BackgroundThe rising prevalence of cognitive impairment among older adults poses a significant public health challenge. While wooden toys are traditionally regarded as tools for cognitive stimulation, research on their potential relationship with cognitive function in older adults remains limited. This study aims to explore the association between engagement with wooden toys and cognitive function in older adults.MethodsA cross-sectional study was conducted in May 2023, involving 387 older adults aged 60–94 years from Yunhe County, Zhejiang Province, China. Both bivariate analysis and multivariable linear regression analysis were performed to assess the association between wooden toy engagement and cognitive function.ResultsAmong the participants, 22.2% reported having experience with wooden toys. Older adults who played with wooden toys regularly or occasionally demonstrated significantly better cognitive performance compared to those who had never played. Importantly, the association between toy engagement frequency and cognitive function varied across age groups. Specifically, adults aged 60–64 who engaged with wooden toys regularly scored higher on the cognitive function than those who did not. Similarly, participants aged 65–69 who played regularly or occasionally also exhibited superior cognitive scores. Multivariable linear regression analysis confirmed that participation in wooden toy activities was positively associated with cognitive function (B = 0.86, 95% CI: 0.14–1.57 in the MMSE model; B = 0.99, 95% CI: 0.16–1.83 in the MoCA model).ConclusionThis study highlights a positive association between engagement with wooden toys and cognitive function in older adults. The frequency of engagement emerged as a critical factor in this relationship, with higher levels of participation linked to better cognitive outcomes. These findings offer valuable insights for developing strategies and policies to prevent or slow cognitive decline in aging populations. Promoting simple, accessible activities such as playing with wooden toys may serve as an effective intervention to enhance cognitive health among older adults.